ANALOGUE MODELS OF TRANSPRESSIVE SYSTEMS - Casas A.M.; Gapais D.; Nalpas T.; Besnard K.; Roman-Berdiel T. (My University, 2001)
This paper presents three series of analogue models of transpressional deformation in a brittle/ductile system: (1) simple transpression, (2) transpression combined with erosion of uplifted areas of the hanging wall above the deformation front, and (3) transpression combined with erosion of the hanging wall and sedimentation at the foot of uplifted zones. In each series of experiments, different convergence angles α, from 0° (pure wrenching) to 90° (pure thrusting) were applied to the models. Results show a sharp contrast between structures formed at α=<15° (wrench-dominated transpression) and α=<30° (thrust-dominated transpression). For a low convergence/strike-slip ratio (0°=<α=<15°), the deformation is localized and structures are typical of a strike-slip regime (R and Y faults). For higher convergence angles (30°=<α=<90°), the deformation is similar for all models, with an elongate asymmetric uplift showing fault-propagation-fold geometries and flanked by thrust-wrench faults. Fault dips also show a significant change from more than 70° for α=<15° to less than 40° for α>30°. For α=<30°, the geometry of the main faults at the borders of the uplift zone is modified by P faults. In experiments with erosion and sedimentation, and thrust-dominated transpression, new faults with increasing dips form during progressive deformation, branching on the main fault at the base of the model.
Keywords: TRANSPRESSION; ANALOGUE MODELLING; EROSION; SEDIMENTATION